Respuesta :

[tex]undefined[/tex]

Explanation:

We would apply the slope formula:

slope = change in y/change in x

change in y = 4 - 0 = 4

change in x = 6 - 0 = 6

Also note on the graph, the change in y is represented by y. And the change in x is represented by x

[tex]\begin{gathered} slope=\frac{4}{6} \\ \text{slope =}\frac{y}{x} \end{gathered}[/tex]

Equating both:

[tex]\begin{gathered} \frac{y}{x}=\frac{4}{6} \\ \frac{y}{x}=\frac{2}{3} \end{gathered}[/tex]

Multiply both sides by x:

[tex]\begin{gathered} \frac{y}{x}\times x=\frac{2}{3}\text{ }\times\text{ x} \\ y\text{ = }\frac{2x}{3}\text{ (option B)} \end{gathered}[/tex]